1999
DOI: 10.7901/2169-3358-1999-1-751
|View full text |Cite
|
Sign up to set email alerts
|

Bioremediation of Oil-Contaminated Fine Sediments

Abstract: Bioremediation of oil contamination has been shown to be effective for cobble and sandy shorelines. To assess the operational limitations of this technology, this project studied its potential to treat buried oil in fine sediments. The effectiveness of bioremediation by nutrient enrichment with water-soluble mineral fertilizers was quantified experimentally with a randomised block design with three replicate blocks. Each block consisted of an untreated control plot, a plot treated with fertilizer alone, an oil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The most intense phase of biodegradation is usually coupled with increased biological activity (Marge sin and Scinner, 1997). Swannell et al (1995) reported a notable increase in the numbers of heterotrophs as a result of continuous addition of nutrients, compared with unfertilized oil-contaminated control in shore line simulating conditions. In cold alpine environment, significant decontamination of diesel oil contaminated soil was observed by Margesin and Schinner (2001).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The most intense phase of biodegradation is usually coupled with increased biological activity (Marge sin and Scinner, 1997). Swannell et al (1995) reported a notable increase in the numbers of heterotrophs as a result of continuous addition of nutrients, compared with unfertilized oil-contaminated control in shore line simulating conditions. In cold alpine environment, significant decontamination of diesel oil contaminated soil was observed by Margesin and Schinner (2001).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, other types of microbial methods have been applied to monitor the microbial activity in the contaminated soil. The re-150 sidual hydrocarbon concentration has been observed to correlate well with different microbial parameters such as microbial counts, respiration, and enzyme activities (Margesin and Schirmer, 2001;Swannell et al, 1995;Ramstadt et aI., 1995). In this study the ATP content, SIR, and number of heterotrophic bacteria in sand column were determined.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pande et al [11] used the second of these indices to monitor biodegradation of crude oils, obtaining a spread of values from 200 for the freshest oil to 4.3 for the most degraded. Swannell et al [23] used variation in the latter two indices to monitor the biodegradation of an Arabian crude oil. Significant shifts were recorded in the value of the ratio of total alkyl polycyclic aromatic hydrocarbons to 17α( H ), 21 β( H )‐hopane, which decreased from 43 in the freshest oil to undetected in the most degraded samples.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, bioremediation has been used on a limited site as part up of the cleanup of the Sea Empress spill [42], and has been demonstrated on experimental spills in marine or brackish environments on the Delaware Bay [43], a Texas wetland [44], a fine-sand beach in England [45], mangroves in Australia [46], and an Arctic shoreline in Spitsbergen [47]. It is likely to be included in responses to future spills where oil strands on rocky or inaccessible shorelines.…”
Section: Shoreline Bioremediationmentioning
confidence: 99%